A novel mechanism of antibody-mediated enhancement of flavivirus infection. - Denise Haslwanter; Dieter Blaas; Franz X Heinz; Karin Stiasny (PLoS Pathogens, 2017)
Antibody-dependent enhancement of viral infection is a well-described phenomenon that is based on the cellular uptake of infectious virus-antibody complexes following their interaction with Fcγ receptors expressed on myeloid cells. Here we describe a novel mechanism of antibody-mediated enhancement of infection by a flavivirus (tick-borne encephalitis virus) in transformed and primary human cells, which is independent of the presence of Fcγ receptors. Using chemical cross-linking and immunoassays, we demonstrate that the monoclonal antibody (mab) A5, recognizing an epitope at the interface of the dimeric envelope protein E, causes dimer dissociation and leads to the exposure of the fusion loop (FL). Under normal conditions of infection, this process is triggered only after virus uptake by the acidic pH in endosomes, resulting in the initiation of membrane fusion through the interaction of the FL with the endosomal membrane. Analysis of virus binding and cellular infection, together with inhibition by the FL-specific mab 4G2, indicated that the FL, exposed after mab A5- induced dimer-dissociation, mediated attachment of the virus to the plasma membrane also at neutral pH, thereby increasing viral infectivity. Since antibody-induced enhancement of binding was not only observed with cells but also with liposomes, it is likely that increased infection was due to FL-lipid interactions and not to interactions with cellular plasma membrane proteins. The novel mechanism of antibody-induced infection enhancement adds a new facet to the complexity of antibody interactions with flaviviruses and may have implications for yet unresolved effects of polyclonal antibody responses on biological properties of these viruses.